Dynamic Approach for Detection of Suspicious Transactions in Money Laundering - A Rao, Anagha; V, Kanchana (International Journal of Engineering and Technology, 2018)
In the previous year, India has been among the most active nations in venturing up the battle against money laundering and related financial and security issues. The effort that likely got the most consideration was â€œdemonetizationâ€ approach which intended to evacuate around 85% of the aggregate illegal cash available for use. To survey India's overall anti-money laundering (AML) system, it's more essential to center on the fundamental legitimate structure set up. In this paper, the proposed methodology is to analyze the user transactions and characterize based on their behavior of transactions. Then it focuses on the characterized transactions and obtains the connectivity among different accounts. To predict the suspicious transactions, we examine the log or trends found in previous years transactions of the user. By comparing the obtained data with the previous data, we will be able to predict suspicious transactions, providing the details are moved for further investigation.Â Â Â